Infinite Integral Involving the Generalized Modified I-Function of Two Variables - Frédéric Ayant; Prvindra Kumar (International Journal for Research in Applied Sciences and Biotechnology, 2021)
In the present paper, we evaluate the general infinite integral involving the generalized modified I-functions of two variables. At the end, we shall see several corollaries and remarks.